Numerical estimation of discharge probability in GEM-based detectors. (2nd September 2021) - Rout, P.K.; Kanishka, R.; Datta, J.; Roy, P.; Bhattacharya, P.; Mukhopadhyay, S.; Majumdar, N.; Sarkar, S.
Abstract: Discharge probability in GEM-based gaseous detectors has been numerically estimated using an axisymmetric hydrodynamic model. Initial primary charge configurations in the drift region, obtained using Heed and Geant4, are found to have significant effect on the subsequent evolution of detector response. Simulation of energy resolution has been performed to establish the capability of the hydrodynamic model to capture statistical nature of the experimental situation. Finally, single and triple GEM configurations exposed to alpha sources have been simulated to estimate discharge probability which have been compared with available experimental data. Despite the simplifying and drastic assumptions in the numerical model, the comparisons are encouraging.